Non-timber forest products from community forestry practices, problems and prospects for livelihood strategy in Jumla - Paudel, Mohan (Banko Janakari, 2009)
Jumla is highly rich in its vast and valuable Non-Timber Forest Products (NTFP) including different kinds of valuable medicinal and aromatic plants. However, in recent years, a significant decrease in availability of commercially traded NTFP species has been experienced. Nevertheless, some important initiatives have also been started to manage NTFPs in a sustainable basis. Community Forestry (CF) is one of these. This study aims to suggest practical and sustainable NTFPs management approach in Jumla analyzing existing roles in livelihood strategy. Study covers CFUGs in Eastern part of the district comprising about 70% CF area and contributes more than 60% of exported NTFPs. PRA and RRA tools were used for data collection in the field. NTFPs were found an integral part of the livelihood strategy in the district. More than 90% food deficit people (57%) were having income from NTFPs as a second source of food arrangement to sustain their livelihood. The average annual income from NTFPs per HH was 18,565. No significant correlation was observed between different social groups and income from NTFPs. But, male were found mostly involved in NTFPs collection comparing female. Beside some promising efforts towards control harvesting of NTFPs, no significant impact of CF was observed. Awareness level of the users and governance aspect of CFUGs were found very poor. There was huge gap between management objectives and management prescriptions of most of the community forests. Key words: NTFPs, Livelihood, management, CFUGs doi: 10.3126/banko.v17i2.2155 Banko Janakari, Vol. 17, No. 2, 45-54